STUDENT PERCEPTIONS ON ENGLISH PRONUNCIATION AFTER TAKING COURSE PHONETICS AND PHONOLOGY - Yousef Bani Ahmad (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2018)
This study aims to find out how students' perceptions of pronunciation after getting the  subject of phonetics and  phonology.  To  answer the formulation of this problem,  researcher  used  a qualitative  descriptive  approach.  Subjects  in  this  study  are  students  of  English  Education University Singaperbangsa Karawang who have taken the course. The data of this study were obtained  from questionnaires were  given to  six  students as respondents.  The results of this study indicates  that respondents  have the  same perception  that English  learners are  greatly assisted   by   phonetics   and   phonology   courses   in   improving   pronunciation,    reducing pronunciation mistakes,  being able to  read  phonetics transcription in the dictionary and  also increase confidence  when speaking English  both in and out of class.